2022
DOI: 10.3390/plants12010127
|View full text |Cite
|
Sign up to set email alerts
|

Convective Drying of Purple Basil (Ocimum basilicum L.) Leaves and Stability of Chlorophyll and Phenolic Compounds during the Process

Abstract: This study evaluated the effect of convective drying on the degradation of color and phenolic compounds of purple basil (Ocimum basilicum L.) leaves, and the hygroscopic behavior of dried leaves. The fresh leaves underwent drying at 40 °C, 50 °C, 60 °C, and 70 °C. Degradation of chlorophyll, flavonoids, and phenolic compounds were evaluated during drying and the hygroscopicity was evaluated through the moisture sorption isotherms. The drying mathematical modeling and the moisture sorption data were performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
3
3
0
Order By: Relevance
“…The results in this point revealed that 40°C is the optimum temperature to achieve the highest yields of the volatile oils distilled from the drying basil and sage using the HSSD that recorded were, 48.43% and 63.05%, respectively. This result is in agreement with the findings of Chaves et al., 2023 who recommended drying purple basil leaves ( O. basilicum L.) at 40°C.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The results in this point revealed that 40°C is the optimum temperature to achieve the highest yields of the volatile oils distilled from the drying basil and sage using the HSSD that recorded were, 48.43% and 63.05%, respectively. This result is in agreement with the findings of Chaves et al., 2023 who recommended drying purple basil leaves ( O. basilicum L.) at 40°C.…”
Section: Resultssupporting
confidence: 93%
“…The results in this point revealed that 40 • C is the optimum temperature to achieve the highest yields of the volatile oils distilled from the drying basil and sage using the HSSD that recorded were, 48.43% and 63.05%, respectively. This result is in agreement with the findings of Chaves et al, 2023 Moreover, applying high drying temperatures commonly led to essential oil % loss. In this concern, our data revealed loss of basil and sage essential oil content was increased by 49% and 35%, respectively, with increasing drying temperature from 40 to 50 • C. This might be because the breaking of oil cells and trichomes may risk rupture due to heating or evaporation, which leads to essential oil loss (Parmar et al, 2018).…”
Section: Effect Of Drying Methods On the Essential Oil Percentagesupporting
confidence: 93%
“…Basil (Ocimum basilicum L.), known in the Amazon region as "common basil", is an aromatic plant species widely used in the traditional diet of the northern region, and in formulations associated with traditional medicine for its antimicrobial, antioxidant, antiinflammatory, anti-hyperglycemic, in addition to the potential for olfactory stimulation, given its richness in volatile compounds, are some of the pharmacological effects attributed to the different constituents of the Ocimum species [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, Brazil and the world have been undergoing major social, cultural, economic, demographic, and technological transformations that result in changes in the health status and pattern of food consumption of the population, characterizing a process called epidemiological transition. In this scenario, the exacerbated intake of ultra-processed foods, which have high levels of preservatives, sodium, sugar, saturated fats, and several other substances, has been considered one of the risk factors that directly contribute to the increase in the rates of chronic non-transmissible diseases (CNCD) such as type 2 diabetes mellitus, cardiovascular diseases, obesity, and systemic arterial hypertension [1][2][3]. NCDs constitute seven of the ten main causes of death in the world, with cardiovascular diseases being the main causes of mortality [6].…”
Section: Introductionmentioning
confidence: 99%
“…In drying processes, the changes in the moisture contents always lead to changes in shapes which are expressed as shrinkage [ 7 , 8 ]. In the process of modeling drying processes, the moisture content and the shrinkage are two significant indicators [ 9 , 10 ]. In recent decades, the different mathematical models of moisture content and shrinkage during drying processes have been studied [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%